2016
DOI: 10.1242/dev.134163
|View full text |Cite
|
Sign up to set email alerts
|

Reelin and cofilin cooperate during the migration of cortical neurons: A quantitative morphological analysis

Abstract: In reeler mutant mice, which are deficient in reelin (Reln), the lamination of the cerebral cortex is disrupted. Reelin signaling induces phosphorylation of LIM kinase 1, which phosphorylates the actin-depolymerizing protein cofilin in migrating neurons. Conditional cofilin mutants show neuronal migration defects. Thus, both reelin and cofilin are indispensable during cortical development. To analyze the effects of cofilin phosphorylation on neuronal migration we used in utero electroporation to transfect E14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 117 publications
4
35
0
Order By: Relevance
“…Chai et al (2009) then demonstrated that the amounts of phosphorylated cofilin are significantly reduced in reeler and that application of recombinant Reelin to reeler tissue significantly increased the phosphorylation of cofilin, suggesting that Reelin-induced cofilin phosporylation is important for the normal lamination of the cerebral cortex. This hypothesis was recently confirmed by in utero electroporation (IUE) experiments (Chai et al, 2016). Transfection of newly born cortical neurons with a non-phosphorylatable form of cofilin ( cofilin S3A ) revealed a significant migration defect of the transfected cells, which remained near their site of origin in the subventricular zone (SVZ)—very much reminiscent of the reeler phenotype.…”
Section: Reelin Acts Upstream Of Cofilin To Facilitate Migrationmentioning
confidence: 75%
See 2 more Smart Citations
“…Chai et al (2009) then demonstrated that the amounts of phosphorylated cofilin are significantly reduced in reeler and that application of recombinant Reelin to reeler tissue significantly increased the phosphorylation of cofilin, suggesting that Reelin-induced cofilin phosporylation is important for the normal lamination of the cerebral cortex. This hypothesis was recently confirmed by in utero electroporation (IUE) experiments (Chai et al, 2016). Transfection of newly born cortical neurons with a non-phosphorylatable form of cofilin ( cofilin S3A ) revealed a significant migration defect of the transfected cells, which remained near their site of origin in the subventricular zone (SVZ)—very much reminiscent of the reeler phenotype.…”
Section: Reelin Acts Upstream Of Cofilin To Facilitate Migrationmentioning
confidence: 75%
“…Sections were counterstained with propidium iodide (PI). Scale bar: 100 μm (from Chai et al, 2016, reproduced with permission).…”
Section: Reelin Acts Upstream Of Cofilin To Facilitate Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…F. Bradke (DZNE, Bonn) kindly provided the Lifeact‐GFP plasmid. M. Kneussel (ZMNH, UKE) kindly provided the EB3‐GFP and X. Chai (from the laboratory of M. Frotscher, ZMNH, UKE) kindly gave us the Cofilin‐GFP and Cofilin‐S3E‐GFP constructs . Cofilin‐S3E‐RFP was a gift from James Bamburg (Addgene plasmid # 50858; http://n2t.net/addgene:50858; ).…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned above, Reelin signaling activates LIMK1, which results in enhanced n-cofilin activation (Chai et al, 2009). A recent study showed that migration defect in the IZ of reeler mice was partially rescued by overexpression of LIMK1 or a phosphomimic mutant of cofilin (Chai et al, 2016). These findings suggest that Reelin signaling influences neuronal migration in the IZ.…”
Section: Roles Of Reelin Signaling In the Radial Migration Of Neuronsmentioning
confidence: 99%